Migrant sanctuaries: a look at African Independent Churches in Johannesburg- local practices within a global city context - Molepo, Mosa Mabohlale (My University, 2020)
ohannesburg is an African city which can be uniquely characterized as a city of migrants. The discovery of gold along the Witwatersrand, resulted in gold mines being excavated all over the province. With this lucrative opportunity for many investors the mines needed a labour force to be maintained, attracting many labour migrants to Johannesburg. Over time Johannesburg became a city which offered a lot of work opportunities for internal migrants, labour migrants and international migrants. With an influx of people coming into the city, over time the city became incapacitated to accommodate this new working population resulting in increased spatial displacement. On the other hand, migrants who entered the city without being accounted for were confronted with social displacement too. At the core of this dialogue is the resulting disorientation and displacement that has occurred over the years and is synonymous with migration globally. People have adapted coping mechanisms in dealing with displacement on spatial and social grounds. Religion, faith and cultural belief plays an important role to mitigate this sense of loss. As one of the case studies the research focused on the presence of African Independent Churches in the city. These groups of people are seen in hidden landscapes of the city on the peripheries. My interest in this group is their capacity as migrants and their exclusion from the formal structures of urban life. Zion Christian Church, which originated in Polokwane, Limpopo, has members who come for work in Johannesburg as labour migrants and migrate in and out of rural life. They seem to use the church to maintain social ties amongst fellow members when in urban areas. This creates a sense of community and is a coping mechanism for dealing with displacement. However, many have witnessed some of these churches operate either in the open or in small structures with inadequacies. The research explores why this is so, as many of these organizations serve as sanctuaries and safe spaces for people. This report problematizes the inability of cities, like Johannesburg, to accommodate groups of people who find themselves in this and similar situations. Earlier we mentioned social displace which is “peoples self-perception of being out of place” (Bakewell, 2008). African Independent Churches use principles of Christian methodology with cultural practices to run their churches. The idea of cultural practices here speaks to rituals and customs which are used to create a sense of identity and pride for people. This report will look at whether there is a link between churches and the value that cultural practices can provide to mitigate social displacement. Presenting churches as the main role players in addressing one of the ways that cities can be accommodating to migrants and vulnerable people. It is expected that not all people will participate in the rituals and custom beliefs of the church. However, this report will aim to present the idea of a sanctuary as an all-encompassing spatial proposal, together with the social participation of churches to address the immediate and long-term needs of migrants in Johannesburg. Globally people migrate into city centers and as a result encounter displacement and because of this, spaces like reception areas are needed. They can be used to provide broader social and civic solutions for the immediate needs of new migrants. Alternatively, this space can be used to provide relief for people who have already been in the city. One of the inquiries will be to investigate where central areas are for migrants (arriving) and local labour migrants already living in Johannesburg are. Then to ultimately present, a sanctuary operated by the church body to accommodate people who are displaced in the city.
A dissertation submitted in fulfilment of the requirements for the degree in Masters in Architecture Professional to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, 2020
Keywords: Independent churches--South Africa; Black people--South Africa--Religion